PENGARUH LOAN TO DEPOSIT RATIO, NET INTEREST MARGIN DAN NONPERFORMING LOAN TERHADAP STABILITAS SISTEM KEUANGAN PERBANKAN DI INDONESIA - Asih Kurniawati; Siwi Nur Indriyani (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study is to determine the effect of loan to deposit ratio, net interest margin, and non-performing loan on thestability of the banking financial system. The population in this study were banks that had an Initial Public Offering on the Indonesia Stock Exchange before March 1, 2016.The sample in this study was determined by purposive sampling technique. All data used is sourced from financial ratio calculation data downloaded from the Financial Services Authority and the Indonesia Stock Exchange Quarterly Financial Report.